Vocabulary : it's all about words working together : an interactive multimedia program to improve senior phase English first additional language learners’ functional vocabulary through an increased understanding of everyday authentic texts and classical and contemporary poetry - Ekron, Anna Cecilia (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Modern Foreign Languages))--University of Stellenbosch, 2008.